The Insidious Threat: Assessing the Dangers and Spread of Tomato Leaf Curl New Delhi Virus - Thuy Thi Bich Vo; Marjia Tabassum; Bupi Nattanong; Muhammad Amir Qureshi; Hyo-jin Im; Giuseppe Parrella; Eui-Joon Kil; Sukchan Lee (The Plant Pathology Journal)
Begomoviruses have significantly threatened many important crops worldwide, causing substantial issues for years. New viruses from this genus are frequently identified, displaying increasingly harmful traits. Among the numerous species within this group, Tomato leaf curl New Delhi virus (ToLCNDV) stands out as a particularly dangerous member due to its notable pathogenic characteristics. This virus poses a serious threat to crops, leading to considerable economic losses. Although ToLCNDV has not been detected in Korea, there is no definitive assurance that it will not appear in the future. Thus, understanding the features and mechanisms of this virus, alongside extensive research on ToLCNDV characteristics and the development of effective preventive strategies, is essential. This review underscores key aspects of ToLCNDV, stressing the risks this virus poses to agriculture. Furthermore, recent advances in breeding natural resistance in key crops are discussed, offering a foundation for improved control methods and preparedness in regions currently unaffected, such as Korea, to mitigate potential agricultural impacts should the virus emerge.